The complete chloroplast genome sequence of Firmina danxiaensis. Issue 1 (2nd January 2020) - Lin, Xiao-Yu; Chen, Zhi-Hui; Yang, Yun-Yuan; Mo, She-Qin; Li, Dong-Lin
Abstract: The complete chloroplast genome of Firmina danxiaensis, an important deciduous tree, was identified and sequenced in this study. The genome size is 161, 205 bp, the GC content is 36.88%. A total of 129 genes were identified, including 84 protein-coding genes, 8 rRNA genes, and 37 tRNA genes. 10 plastome accessions from Sterculiaceae were selected to assess the phylogenetic placement of genus and the result showed that F. danxiaensis is most closely related to F. simplex .